Hubungan Aktivitas Fisik Dan Pola Makan Dengan Upaya Pencegahan Hipertensi Bagi Pengunjung Di UPT Puskesmas Tumbang Samba - Elia, Rosa; Carolina, Putria; Rosela, Kristin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Hypertension is a major non-communicable disease that continues to pose a growing public health challenge. Preventive measures such as maintaining a healthy diet and regular physical activity are known to help reduce the risk of hypertension. However, the extent to which these two factors contribute to hypertension prevention at the primary healthcare level remains unclear. This study aims to determine the relationship between physical activity and diet with hypertension prevention efforts among visitors to the Tumbang Samba Community Health Center (UPT) in 2025. This study used a quantitative approach with a descriptive-analytical design through a cross-sectional method. Data were collected from June 9-16, 2025, for two weeks, and 40 respondents were selected through accidental sampling. Data collection was conducted using a questionnaire. Data were analyzed using the chi-square test with a significance level of 0.05. The results showed that most respondents engaged in light physical activity (82.5%) and had good eating habits (72.5%). In addition, 77.5% of respondents demonstrated high levels of effort in hypertension prevention. The chi-square analysis showed no significant relationship between physical activity and hypertension prevention (p = 0.672), but there was a significant relationship between eating habits and hypertension prevention (p = 0.000). The conclusion shows that eating habits have a significant relationship with hypertension prevention efforts, while physical activity does not. Therefore, health promotion strategies should focus on improving healthy eating behaviors as the primary step in hypertension prevention.